2011
DOI: 10.1186/1472-6904-11-22
|View full text |Cite
|
Sign up to set email alerts
|

Etomidate and mortality in cirrhotic patients with septic shock

Abstract: BackgroundClinical effects and outcomes of a single dose etomidate prior to intubation in the intensive care setting is controversial. The aim of this study is to evaluate the association of a single dose effect of etomidate prior to intubation on the mortality of septic cirrhotic patients and the impact of the subsequent use of low dose hydrocortisone.MethodsThis is a nested-cohort study within a randomized double blind placebo controlled study evaluating the use of low dose hydrocortisone in cirrhotic septic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…All studies included in the mortality analysis reported on vital status at discharge. However, only three additionally described 28-day mortality (5,14,22).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…All studies included in the mortality analysis reported on vital status at discharge. However, only three additionally described 28-day mortality (5,14,22).…”
Section: Resultsmentioning
confidence: 96%
“…These ten studies reported on 1,623 patients with sepsis or septic shock. Of these ten studies, seven evaluated mortality (5,(14)(15)(16)(17)(18)22) and seven assessed the development of AI (5,14,15,(18)(19)(20)(21) (four studies assessed both). Of the ten studies included for meta-analysis, five studies included data from randomized controlled trials (5,14,16,20,22), two were prospective observational studies (17,21), and three were retrospective observational studies (15,18,19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of the ideal anaesthetic/sedative medication in critically ill patients with aortic aneurysm causing mediastinal compression remains unclear. Etomidate has proven to be efficacious in maintaining stable hemodynamics; however, etomidate is a potent inhibitor of adrenal corticsol secretion and has been associated with increased mortality in critically ill patients [10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite clear endocrinological proof of etomidate's potentially adverse effect and worldwide termination of its repetitive use for sedation, the clinical impact of a single‐dose etomidate administration on adrenal insufficiency‐associated and all‐cause mortality remains controversial. A systematic review with meta‐analysis of five RCTs, two prospective and three retrospective observational studies, focusing exclusively on 865 sepsis patients receiving etomidate for rapid sequence intubation concluded that the administration of a single dose of etomidate increased the risk of adrenal insufficiency (relative risk, 1.33) and all‐cause mortality (relative risk, 1.20) in sepsis. The included studies, however, demonstrate obvious limitations in terms of: 1) heterogeneity; 2) small sample size or only subgroup analysis; 3) variation in the type of comparative sedative, severity of illness score, timing to determine adrenal insufficiency; 4) limited quality of study randomisation, blinding, description of inclusion, and exclusion criteria; and 5) discrepancies in follow‐up and reporting of 28‐day mortality.…”
Section: Etomidate – a Unique Agent Among Injected Anaestheticsmentioning
confidence: 99%